An Analysis of Ideology in Translation on Bilingual Story Book for Children - Tania Syafutri; Iis Sujarwati (Yayasan Karinosseff Muda Indonesia, 2021)
This research analyzed the methods, techniques, and ideology in translation on bilingual story book for children entitled “Little Sunshine Bilingual Book. Kumpulan Lagu dan Cerita Anak- Anak Dwibahasa.” The theories were used in this research are from Newmark, Molina Albir, and Venuti. This research intended to analyze the techniques, methods, and ideology in translation on “Little Sunshine Bilingual Book. Kumpulan Lagu dan Cerita Anak- Anak Dwibahasa.” This research was used descriptive qualitative method because the researcher want to analyze verbal text in written form of “Little Sunshine Bilingual Book. Kumpulan Lagu dan Cerita Anak- Anak Dwibahasa”. The source of data in this research was one of text in bilingual story book for children that is “Roro Jonggrang” story. There are several steps of analyzing the data: the first is reading the text entitled “Roro Jonggrang” in “Little Sunshine Bilingual Book. Kumpulan Lagu dan Cerita Anak- Anak Dwibahasa”, the second is taking note of several data that need to analyze such as the phrases or sentences in “Little Sunshine Bilingual Book. Kumpulan Lagu dan Cerita Anak- Anak Dwibahasa” stories, the third is identifying the technique of translation of “Roro Jonggrang” story in “Little Sunshine Bilingual Book. Kumpulan Lagu dan Cerita Anak- Anak Dwibahasa.”, the fourth is observing which the technique of translation that often use in “Roro Jonggrang” story in “Little Sunshine Bilingual Book. Kumpulan Lagu dan Cerita Anak- Anak Dwibahasa” to know about the method that use in translation of this story, the last is after gaining the method that use in translation of this story, the researcher would know about ideology of this translation.